Cutaneous adnexal adenocarcinoma with exquisite sensitivity to trastuzumab. Issue 5 (22nd February 2017) - Brown, Timothy J.; Sher, David J.; Nedzi, Lucien A.; Hughes, Randall S.; Beg, Muhammad S.; Mull, Jason; Sarode, Venetia R.; Khan, Saad A.
ABSTRACT: Background: Cutaneous adnexal adenocarcinoma is a rare cancer that is occasionally human epidermal growth factor receptor‐2 (HER‐2)‐positive, and demonstrates variable response to HER‐2 inhibitors. Methods: We report a case of adnexal adenocarcinoma of the scalp in a 56‐year‐old man. He underwent wide local excision with cervical node dissection followed by radiation, but had extensive local recurrence. Results: Pathology demonstrated a poorly differentiated adnexal adenocarcinoma with HER‐2 overexpression by immunohistochemistry (IHC) and high HER‐2 gene amplification by fluorescence in situ hybridization. The patient was treated with trastuzumab‐based therapy with dramatic response and clinical resolution of the tumor. Upon pausing trastuzumab, he developed local relapse, but had an excellent response to restarting trastuzumab monotherapy. He lacks visible disease 43 months after the initial diagnosis. Conclusion: We believe the exquisite sensitivity of the primary carcinoma and subsequent recurrence to trastuzumab therapy was due to strong HER‐2 expression both at the protein and gene level. © 2017 Wiley Periodicals, Inc. Head Neck 39: E69–E71, 2017